Reactivity of an aryl-substituted silicon-silicon triple bond: 1,2-disilabenzenes from the reactions of a 1,2-diaryldisilyne with alkynes - Han, Joon Soo; Sasamori, Takahiro; Mizuhata, Yoshiyuki; Tokitoh, Norihiro (ROYAL SOC CHEMISTRY, 2010)
The reactivity of a diaryl-substituted disilyne, Ar-Si Si-Ar, with alkynes was examined. Reaction of the disilyne with acetylene yielded a 1,2-disilabenzene as the sole product.
Keywords: DISILYNE RSISIR R; 1,4-DIAZA-2,3-DISILABENZENE ANALOG; CRYSTAL-STRUCTURE; DISILENES; AROMATICITY; CHEMISTRY; SILABENZENE; COMPOUND; ROUTE; RINGS